Analyzing the Influence of Accessibility and User Factors on Mode Choice for Daily Commuters - Fathoni, Syahrul; Widyastuti, Hera (Research Horizon, 2025)
The population growth of Surabaya City is increasing every year with a growth rate of 0.42% in the range of 2020-2023. However, the increase is also in line with the increase in private vehicles and travel needs, it is inversely proportional to the lack of optimal use of public transportation, especially Trans Semanggi Suroboyo. Trans Semanggi Suroboyo West-East corridor crosses residential areas to the city center, so it is expected to connect residences with places of education and work. One of the causes of this non-optimality based on previous research is the accessibility factor. This study aims to explore accessibility-related influences on mode choice. The methodology used in this study is the assessment of accessibility levels using the public transport accessibility levels method and continued with mode selection using the binary logistic regression method. The results of this study show that there is evidence of the influence of accessibility in the selection of transportation modes. In addition, there are variables of user characteristics that influence the selection of modes that complement the model. This study has potential as an evaluation material in improving accessibility to support the optimization of the use of public transportation, especially on daily trips.